2021
DOI: 10.24036/10354171074
|View full text |Cite
|
Sign up to set email alerts
|

Design and Validity of Physics Teaching Materials Based on Cognitive Conflict Integrated Virtual Laboratory in Atomic Nucleus

Abstract: Curiculum.2013 requires.the students to be able to improve.the understanding of a.concepts. But it stil not realizet One of the solutions of this problem is to make physics teaching.materials based on cognitive conflicts on atomic nucleus to improve students’ conceptual understanding. The purpose.of this a research is to produce a valid cognitive conflict-based teaching material design. The type of research is Design / Development Research usingn the Plomp model. However, this research is limited to theaPrelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 10 publications
6
16
0
Order By: Relevance
“…Experimental activities will also encourage students to find learning concepts that are correct and based on scientific facts so that they can improve students' understanding of concepts and avoid misconceptions. concepts (Delvia, et al, 2021).…”
Section: Concept Understandingmentioning
confidence: 99%
“…Experimental activities will also encourage students to find learning concepts that are correct and based on scientific facts so that they can improve students' understanding of concepts and avoid misconceptions. concepts (Delvia, et al, 2021).…”
Section: Concept Understandingmentioning
confidence: 99%
“…A research instrument is a tool used to measure the observed natural and social phenomena. The research instruments used were compiled by themselves and their validity will be tested [10]. Based on the purpose of the research conducted, a research instrument is needed to analyze the questions in the form of an analysis sheet in the form of a statement regarding the HOTS indicators on Physics questions for high schools in Agam district.…”
Section: Methodsmentioning
confidence: 99%
“…The research instrument used was compiled and tested for validity. To develop a good instrument, it is necessary to take several steps [12], namely: 1. Planning, the stages of goal formulation, determining the variables, and their categories.…”
Section: Methodsmentioning
confidence: 99%